Subcutaneous phycomycosis mimics elephantiasis. - M. Riganti (2018)
A case of subcutaneous phycomycosis involving the right thigh for 1 year duration which mimic elephantiasis was reported in a 21-year-old military man. An initial diagnosis was that of a subcutaneous tissue lesion attributed to parasitic manifestation but turned out to be that of subcutaneous fungal infection both clinically and histologically. The lesion was successfully treated with cotrimoxazole for a period of one month, and followed up for 4 1/2 months with complete cure.